Impact of Carbapenem Resistance Enterobacterales (CRE) on Human Health: Bangladesh Perspective - Begum, Mosammat Fahmida; Nasrin, Mahfuza (Bangladesh Journal of Medical Microbiology, 2025)
Abstract Not Available Bangladesh Journal of Medical Microbiologist, January 2025;19(1):1-3